Nutritional immunology: function of natural killer cells and their modulation by resveratrol for cancer prevention and treatment. Issue 1 (December 2015) - Leischner, Christian; Burkard, Markus; Pfeiffer, Matthias; Lauer, Ulrich; Busch, Christian; Venturelli, Sascha
Abstract Natural killer (NK) cells as part of the innate immune system represent the first line of defence against (virus-) infected and malignantly transformed cells. The emerging field of nutritional immunology focuses on compounds featuring immune-modulating activities in particular on NK cells, which e.g. can be exploited for cancer prevention and treatment. The plant-based nutrition resveratrol is a ternary hydroxylated stilbene, which is present in many foods and beverages, respectively. In humans it comprises a large variety of distinct biological activities. Interestingly, resveratrol strongly modulates the immune response including the activity of NK cells. This review will give an overview on NK cell functions and summarize the resveratrol-mediated modulation thereof.